2019
DOI: 10.1111/jace.16721
|View full text |Cite
|
Sign up to set email alerts
|

Controllable ultra‐broadband visible and near‐infrared photoemissions in Bi‐doped germanium‐borate glasses

Abstract: The design of functional materials with tunable broadband luminescence performance is still of great interest in the fields of lighting, solar cells, tunable lasers, and optical amplifiers. Here, via a melt‐quenching method, a series of bismuth (Bi)‐doped germanium‐borate glasses with composition of 40GeO2–25B2O3–25Gd2O3–10La2O3–xBi2O3 have been prepared, in which multiple Bi active centers can be stabilized simultaneously. Dual‐modulating modes of visible (380‐750 nm) and near‐infrared (NIR) (1000‐1600 nm) br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 46 publications
(112 reference statements)
0
8
0
Order By: Relevance
“…Bi 3+ ions can emit various light from blue to red in inorganic compounds. , Moreover, the photoluminescence excitation (PLE) band of Bi 3+ usually locates in the n-UV region, which can effectively avoid the spectral reabsorption phenomenon, thus increasing the luminous efficiency . It was reported that some Bi 3+ -functionalized aluminoborate and germanium-borate glasses can emit broad-band NIR emission (800–1600 nm), but the low transmittance of glasses limits the large-scale applications. Besides, the NIR emission of Bi 3+ -activated phosphors is seldom reported, except for BaBPO 5 :Bi 3+ phosphors .…”
Section: Introductionmentioning
confidence: 99%
“…Bi 3+ ions can emit various light from blue to red in inorganic compounds. , Moreover, the photoluminescence excitation (PLE) band of Bi 3+ usually locates in the n-UV region, which can effectively avoid the spectral reabsorption phenomenon, thus increasing the luminous efficiency . It was reported that some Bi 3+ -functionalized aluminoborate and germanium-borate glasses can emit broad-band NIR emission (800–1600 nm), but the low transmittance of glasses limits the large-scale applications. Besides, the NIR emission of Bi 3+ -activated phosphors is seldom reported, except for BaBPO 5 :Bi 3+ phosphors .…”
Section: Introductionmentioning
confidence: 99%
“…Glasses containing bismuth have thus far been proposed in applications such as broadband high gain optical amplifiers, tunable lasers, and fibers; , however, Bi 3+ ions can also function as sensitizers to increase the efficiency of energy transfer to rare earth ions for specific photovoltaic applications . Numerous bismuth-containing systems have been prepared on germanate, silicate, phosphate, borate, and oxyfluoride glass bases and characterized with respect to their physical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, Bi 2+ may exist as nonluminescent centers in the glasses discussed in this study. In addition, the lifetime of Bi 3+ in crystals is normally in the range of 10 −5 –10 −8 s. In our previous report, we observed a lifetime of ∼1 μs in Bi‐doped aluminate glasses, which is in the same order of magnitude as the luminescence lifetime of bismuth in germanate glasses and phosphors, especially for aluminate phosphors 70–72 . Thus, we tend to attribute this emission to the 3 P 1 → 1 S 0 transition in Bi 3+ 73 .…”
Section: Resultsmentioning
confidence: 68%
“…In addition, the lifetime of Bi 3+ in crystals is normally in the range of 10 −5 -10 −8 s. In our previous report, we observed a lifetime of ∼1 μs in Bidoped aluminate glasses, which is in the same order of magnitude as the luminescence lifetime of bismuth in germanate glasses and phosphors, especially for aluminate phosphors. [70][71][72] Thus, we tend to attribute this emission to the 3 P 1 → 1 S 0 transition in Bi 3+ . 73 With the introduction of higher amounts of GeO 2 , the emission intensity of this band continuously decreases, which is accompanied by a blue-shift from about 490 to 410 nm, as seen in Figure 6C.…”
Section: Resultsmentioning
confidence: 97%